0505 EMR and Clinic Based Approaches for Recruiting Peer Support for Sleep Apnea. (12th April 2019) - Provencio, Natalie; Morton, Christopher J; Wendel, Christopher; Berryhill, Sarah; Partha, Meghana T; Kulkarni, Hrishikesh; Combs, Daniel; Patel, Salma I; Desai, Bhavim; Quan, Stuart F; Parthasarathy, Sairam
Abstract: Introduction: Peer-support can improve adherence to therapy in various chronic medical conditions including adherence to continuous positive airway pressure (CPAP) therapy in patients with obstructive sleep apnea. Methodology to identify and recruit peers are generally not well described. We assessed the feasibility and yield of Electronic Medical Record (EMR) based approaches versus clinic-based approaches for identifying and recruiting peers with OSA who can help promote adherent behavior in research participants. Methods: Peer-mentors were recruited from the sleep center by a stepped EMR-based approach combined with a clinic-based approach or direct referral of potential mentors by busy clinicians within these clinics. Results: Over an 11-month period, 1, 539 sleep clinic patients with upcoming appointments were screened in the combined EMR- and clinic-based approaches. Forty-five percent (n=694) of 1, 539 patients (51.8% women) were initially identified as potential peer-mentors. A more detailed EMR-review deemed 86.4% (n=600) of the patients as ineligible to be peer-mentors. Reasons for exclusion included: mental health conditions (26.2%); nonadherence to CPAP therapy based on device download (23%); complicated medical history (12.7%); recently diagnosed with OSA or undergoing diagnostic work-up (11.6%); residing outside city limits (11.8%); no OSA diagnosis (9.7%); shift-work or busy job interfering with mentoring responsibilities (2.6%); provider documented difficulty with CPAP adherence (1.7%); and oral appliance treatment (0.9%). Of the remaining 94 individuals, 11 consented to participating in the research study as peer-mentors when approached in the sleep clinic. EMR-based screening was more efficient in detecting screen-failures (93.8%) than clinic-based approach of detecting screen-failures (83%; χ2 P<0.0001). Recruitment rate of the combined EMR- and clinic-based screening approach was 11 of 1, 539 (0.01%) whereas direct referrals by busy clinicians had a recruitment rate of 100% (six of six referred patients consented for study participation as peer mentors; P<0.0001). Conclusion: An EMR-based identification of potential peer-mentors for promoting adherent behavior in patients with OSA is feasible and can be combined with clinic-based approaches. Support (If Any): HL138377